The Relationship between Language Learning Strategies used by Vocational Students and Level of Proficiency - Yustitiasari, Hilda; Junining, Esti; Sahiruddin, Sahiruddin (e-Journal of Linguistics; Vol 14 No 1 (2020): e-jl JanuaryDO - 10.24843/e-jl.2020.v14.i01.p13, 2020)
The vocational college students instructed by the teacher to used self-directed learning in learning English outside classroom or during the internship. Due to the requirement of graduation which they should pass the TOEFL test after the internship. The self-directed learning is exercised by managing students’ Language Learning Strategies (LLS) which known could improve language proficiency. Hereby, this study identifies: (1) the language learning strategy used by vocational college learners based on high and low proficient, (2) the relationship between language learning strategy and English proficiency of high proficient, (3) the relationship between language learning strategy and English proficiency of high proficient. The participant of this study is 52 students of Politeknik Kota Malang which willing to complete the Strategy Inventory of Language Learning (SILL) and done the TOEFL test. This study employed correlational research design to identify the relationship between variables which is multiple regression analysis employed in this study. There are six strategies of language learning strategies by Oxford (1990) as the independent variables (predictors) and English proficiency (criterion) as the dependent variable. The result showed that Although, language learning strategy cannot simultaneously predict the English proficiency of high proficient and low proficient, compensation strategy reported as high frequently used by high proficient learners. While metacognitive strategies reported used by low proficient learners.